2015
DOI: 10.1016/j.beproc.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral evidence illuminating the visual abilities of the terrestrial Caribbean hermit crab Coenobita clypeatus

Abstract: a b s t r a c tHermit crabs hide into shells when confronted with potential dangers, including images presented on a monitor. We do not know, however, what hermit crabs can see and how they perceive different objects. We examined the hiding response of the Caribbean hermit crab (Coenobita clypeatus) to various stimuli presented on a monitor in seven experiments to explore whether crabs could discriminate different properties of a threatening digital image, including color, brightness, contrast, shape and orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For example, evidence is mixed as to whether pigeons (Columba livia) can perceive the pictorial or representational aspects of pictorial displays (Fagot, 2000). We've found evidence that the Caribbean hermit crab lacks color vision (Ping et al, 2015). Unpublished studies from our lab also fail to find evidence that hermit crabs can distinguish between pictorial content that is naturalistic (e.g., photographs of a hawk, coconut crab, sea gull), man-made real objects (e.g., a…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, evidence is mixed as to whether pigeons (Columba livia) can perceive the pictorial or representational aspects of pictorial displays (Fagot, 2000). We've found evidence that the Caribbean hermit crab lacks color vision (Ping et al, 2015). Unpublished studies from our lab also fail to find evidence that hermit crabs can distinguish between pictorial content that is naturalistic (e.g., photographs of a hawk, coconut crab, sea gull), man-made real objects (e.g., a…”
Section: Discussionmentioning
confidence: 84%
“…Caribbean terrestrial hermit crabs (Coenobita clypeatus) are an ideal invertebrate system to test looming image discrimination and processing. Prior work in our lab demonstrated that hermit crabs have a binary escape response; they hide (or fail to hide) in their shells when presented with a looming image of a predator or geometric shape presented on a computer screen (Chan et al 2010b;Ping et al, 2015;Ryan et al 2012;Stahlman et al 2011;Watanabe et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A key criterion for a signal, including a signal of RHP, is that recipients must be able to perceive and hence respond to the signal ( Searcy and Nowicki 2005 ; Bradbury and Vehrencamp 2011 ; Laidre and Johnstone 2013 ). Interestingly, laboratory experiments in terrestrial hermit crabs have revealed that individuals can differentiate artificial red coloration from blue and green coloration ( Ping et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, evidence is mixed as to whether pigeons ( Columba livia ) can perceive the pictorial or representational aspects of pictorial displays ( Fagot, 2000 ). We’ve found evidence that the Caribbean hermit crab lacks color vision ( Ping et al, 2015 ). Unpublished studies from our lab also fail to find evidence that hermit crabs can distinguish between pictorial content that is naturalistic (e.g., photographs of a hawk, coconut crab, sea gull), man-made real objects (e.g., a picture of a couch), and simple geometric shapes (e.g., a square, star, or oval).…”
Section: Discussionmentioning
confidence: 99%
“…Caribbean terrestrial hermit crabs (Coenobita clypeatus ) are an ideal invertebrate system to test looming image discrimination and processing. Prior work in our lab demonstrated that hermit crabs have a binary escape response; they hide (or fail to hide) in their shells when presented with a looming image of a predator or geometric shape presented on a computer screen ( Chan et al, 2010b ; Ping et al, 2015 ; Ryan et al, 2012 ; Stahlman et al, 2011 ; Watanabe et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%